PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN SIWALAN (TRIBUNG) DI DUSUN LEMBANA DESA BANCAMARA KECAMATAN DUNGKEK KABUPATEN SUMENEP - Imron Sadewo; Sayyid Alwi Zaen; Ahmad fauzan; M Jamaluddin Mashuri (STAI Nurul Huda Kapongan Situbondo, 2023)
Community empowerment can be interpreted as a process that builds a community or group of people that departs from their own will and initiative, which can be in the form of capacity building, grouping and all forms of community behavior change. One of the community empowerment is community empowerment through the utilization of siwalan water treatment into tribung sugar in Lembena hamlet, Bancamara village. By optimizing the synergy of the Ansor Youth Movement with the Lembena hamlet community, Bancamara village which is dominated by farmers and fishermen. The reasons for choosing the use of cow dung include: 1) Considering the population of Lembena hamlet, Bancamara village, 50% of whom work as farmers and fishermen, 2) Seeing the situation that almost every yard in people's homes has a palm tree, 3) taking advantage of the existing potential namely siwalan tree, 4) Processing costs are not too expensive, 5) The ingredients can be directly found, 6) tribung sugar if consumed continuously will be able to reduce the pressure on the cost of granulated sugar which is so expensive and productive for the community. From initial observations it was found that the people of Lembena hamlet, Bancamara village did not use and process siwalan water wisely and did not understand the advantages of tribung sugar and were more interested in granulated sugar. The results of the service at the STAINH 2022 KKN Posko I are able to provide public understanding of the advantages and conveniences in the processing process, and the Ansor Youth Movement is willing to accommodate the community's processed tribung sugar products and receive a supply of raw siwalan water from the residents of Lembena hamlet, Bancamara village.